Analisis Determinan Pendapatan Petani Padi Di Kecamatan Bungaya Kabupaten Gowa - Juardi Juardi; Sri Artati Salju; Baso Iwang (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2022)
The purpose of this study was to determine how much influence the area of ​​land, selling prices, production yields and production costs have on the income of rice farmers in Bungaya District, Gowa Regency. This research was conducted in Sapaya Village, Bungaya District, Gowa Regency. This type of research is quantitative and descriptive in nature, the data is processed according to the needs of the model used. The source of this research data comes from the BPS district. Gowa, related agencies (Horticultural Food Crops & Department of Agriculture, Gowa regency), observation, interviews, documentation, and data collection sheet (questionnaire). The total population in this study is 230 people and the number of samples is 146 respondents. With data processing techniques, namely using the classic assumption test and hypothesis testing, and analyzing data using multiple linear regression with the help of SPSS 21. The results showed that simultaneously the variables of land area, selling price, production yields, and production costs had a significant and positive effect on farmers' income. Most of the land area, selling price, and production yields have a significant and positive relationship with farmers' income. Meanwhile, production costs are partially negatively and not significantly related to the income of rice farmers. The coefficient of determination (RSquare) of 0.972 indicates that the proportion of rice farmers' income variations that can be explained by variations in the independent variables, namely land area, selling price, production price, and production costs is 97.2% while the remaining 2.8% is influenced by the variables other variables not discussed in this study.